2020
DOI: 10.1017/s0143814x20000045
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in policy implementation: caste and electrification in rural India

Abstract: We examine unequal outcomes in the implementation of India’s national rural electrification program in Uttar Pradesh. We ask two questions: (1) to what extent did Dalits, the lowest group in India’s caste hierarchy, receive less attention when the state electrified rural communities? (2) Was BSP, the state’s Dalit party, able to reduce this inequality? Using data from a hundred thousand villages, we provide robust evidence for unequal outcomes. Villages inhabited solely by Dalits were 20 percentage points less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…10 Dugoua et al [2017] addressed the issue of caste-based social exclusion by looking at the differential effect of the RGGVY on the likelihood of electrification by caste groups at the village level for six relatively poorer states in India. Aklin et al [2020] looked at the caste based electrification rate in Uttar Pradesh between 2001 to 2011. Both studies found that the likelihood of electrification was significantly higher for villages with more forward caste communities than Dalit (SC) communities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Dugoua et al [2017] addressed the issue of caste-based social exclusion by looking at the differential effect of the RGGVY on the likelihood of electrification by caste groups at the village level for six relatively poorer states in India. Aklin et al [2020] looked at the caste based electrification rate in Uttar Pradesh between 2001 to 2011. Both studies found that the likelihood of electrification was significantly higher for villages with more forward caste communities than Dalit (SC) communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Socioeconomic disparities between dominant and marginalized groups has been widely documented in India [Thorat and Neuman, 2012, Drèze and Sen, 2013, Thorat et al, 2017, Zacharias and Vakulabharanam, 2011. However, less is understood about the effects of public policies on these disparities [Aklin et al, 2020, Kennedy et al, 2019, Pelz et al, 2020. Social discrimination can have negative welfare impacts, but can public policies counter these effects?…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations